Effects of energy level on methionine utilization by growing steers - G.F. Schroeder; M.S. Awawdeh; D.P. Gnad; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2004)
The objective of this study was to evaluate the effect of energy level on amino acid utilization in growing steers. Six ruminally cannulated Holstein steers (503 lb) were limit-fed (6.2 lb/day dry matter) a diet based on soybean hulls (83%), wheat straw (7.6%), and cane molasses (4.1%). The treatments consisted of the infusion of two methionine levels (0 or 3 g/d) and three energy levels (0, 1.3, or 2.6 Mcal ME/day) in a 2 x 3 factorial arrangement. Energy was supplied through ruminal infusion of acetate, propionate, and butyrate and through abomasal infusion of glucose and fat in increasing amounts. No interactions between methionine and energy level were observed. Nitrogen balance was increased by methionine supplementation, indicating that this amino acid limited protein deposition. A linear increase in nitrogen retention was found with the increase in energy. These improvements in protein deposition were related to reductions in urinary nitrogen excretion, reduced plasma-urea concentrations, and greater circulating concentrations of insulin and insulin-like growth factor-I. The results of this study suggest that amino acid utilization can be improved by increasing energy. These effects could be partly explained by variations in plasma concentration of key hormones involved in the control of protein deposition.
Keywords: Cattlemen' s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Methionine; Steers; Cannulated